2011
DOI: 10.1111/j.1365-313x.2011.04576.x
|View full text |Cite
|
Sign up to set email alerts
|

Bundle‐sheath cell regulation of xylem‐mesophyll water transport via aquaporins under drought stress: a target of xylem‐borne ABA?

Abstract: SUMMARYThe hydraulic conductivity of the leaf vascular system (K leaf ) is dynamic and decreases rapidly under drought stress, possibly in response to the stress phytohormone ABA, which increases sharply in the xylem sap (ABA xyl ) during periods of drought. Vascular bundle-sheath cells (BSCs; a layer of parenchymatous cells tightly enwrapping the entire leaf vasculature) have been hypothesized to control K leaf via the specific activity of BSC aquaporins (AQPs). We examined this hypothesis and provide evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
340
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(372 citation statements)
references
References 34 publications
(48 reference statements)
23
340
3
Order By: Relevance
“…These protoplasts were found to have low basal (background) P f levels 7 and can serve as a functional-expression system to enable reproducible P f measurements.…”
Section: Representative Resultsmentioning
confidence: 99%
“…These protoplasts were found to have low basal (background) P f levels 7 and can serve as a functional-expression system to enable reproducible P f measurements.…”
Section: Representative Resultsmentioning
confidence: 99%
“…When WT Arabidopsis leaves were xylem-supplied with 10mM ABA, leaf hydraulic conductance (K leaf ) decreased by c. 50%, yet foliar application of the same ABA concentration (while decreasing transpiration rate) had no statistically significant effect on detached leaf K leaf . 12 While application ABA to root medium generally inhibit root growth, McAdam et al recently shown that shoot-derived ABA promotes root growth. 43 It is clear that the different sourced ABA correspondence to its distinct action, even in the same tissues or cells.…”
Section: Spatio-temporal Specificities Of Pyr1/pyl/rcar Aba Receptorsmentioning
confidence: 99%
“…21 While PYL8 mediates the ability of ABA to inhibit primary root growth through the PP2C-SnRK2 pathway, 18 it together with PYL9 promotes lateral root growth recovery from inhibition independently of the core signaling pathway by enhancing MYB77-dependent transcription of auxin-responsive genes. 17,23 The cell-specificities of PYR1/PYL/RCAR ABA receptors It has been shown that application ABA directly enhance plasma membrane water permeability of roots cortical cells 15 and guard cells, 24 while inhibit that of vascular bundle-sheath cells 12 and has not effect to that of mesophyll cells. 12,24 The core signaling component SnRK2.6 has been documented implicated in plasma membrane intrinsic proteins PIP2;1 activation through protein phosphorylation at Ser-121, thus increase in guard cell permeability to water.…”
mentioning
confidence: 99%
See 2 more Smart Citations